THE AFTERMATH OF THE ARAB SPRING AND ITS IMPLICATION FOR PEACE AND DEVELOPMENT IN THE SAHEL AND SUB-SAHARAN AFRICA (The Strategic Review for Southern Africa, 2020)
The Arab Spring, which brought an end to the authoritarian regimes in Tunisia, Egypt and Libya, was greeted with so much expectation, especially as it gave hope for the expansion of democracy. Unfortunately, however, the Arab Spring has only helped to bring about a period of political uncertainty in the affected countries and created the opportunity for political instability in the Sahel and Sub-Saharan Africa. The fragility of states in Africa with the attendant governance deficits have also created the platform for non-state armed actors to penetrate the Sahel and Sub-Saharan Africa, which ultimately impacts negatively on the region. This study, therefore, seeks to investigate the implication of the Arab Spring for peace and development in the Sahel and SubSaharan Africa.